Weed nutrient content in commercial orange orchards in the region of Manaus, Amazonas - Sanches, Giulia Ketlen; Silva, Maria Rosangela Malheiros; Adjeran, Oloukemi Karmen Jocelyne [UNESP]; Tucci, Carlos Alberto Franco; Silva, José Ferreira (Centro Universitario de Maringa, 2024)
Weeds compete for nutrients causing productivity losses with crops, so the quantification of nutrients in these plants can indicate their nutrient absorption efficiency. In this research we aim to identify weed species representative of three commercial orange orchards (Citrus sinensis L.) in the region of Manaus (AM), and to determine their potential for nutrient absorption. A survey of the floristic composition of orchards was carried out from August to October in 2019, and the phytosociological indicators of species were identified. The main species were selected according to the Importance Value Index (IVI). Weeds and C. sinensis leaves samples were analyzed to obtain nutrient contents. Weeds showed competitive potential in commercial orange orchards, once they had a high nutrient content in their dry matter. Weeds with greater amounts of nutrients were Alternanthera Ficoidea (L.) P. Beauv. (N, K, Mg, Cu, Mn and Zn), Commelina benghalensis L. (P, S and Fe), Pseudelephantopus spiralis (Less.) Cronquist (N, P, K, Mg, Fe and Zn), Acalypha arvensis Poepp. (P and Ca), Cyperus diffusus Vahl (Fe and Mn) and Stachytarpheta cayennensis (Rich.) Vahl (Mg and Zn).
Teor de nutrientes em plantas daninhas de pomares de laranjeiras da região de Manaus, Amazonas
Keywords: Citrus sinensis L; Competition; Mineral nutrition; Plant communities